Electrochemical production of methanol and hydrogen from biomass waste - Zichun Xiong; Kazuyo Kobayashi; Aki Miyawaki; Shinya Teranishi; Takashi Hibino (Electrochemistry Communications)
This paper reports an electrochemical approach that uses unused or discarded biomass as a resource for renewable and sustainable methanol and hydrogen production. The biomass feedstocks tested were lignosulfonate, newspaper, pampas grass, and bamboo. Methanol was extracted through the demethylation of methoxy groups of lignin in biomass at the anode. The advantages of this method are that (1) electrolysis proceeds under mild conditions of 75 °C, atmospheric pressure, and relatively low voltage, (2) hydrogen is produced at the cathode, irrespective of the type of biomass, and (3) the residue after electrolysis can be used as fuel.